Civil liability arising from production of pharmaceutical factories - Fathil AbdulWahab , Hossam; Abdulbaqi Yusef, Assist.Prof. ltidal (Basra studies journal, 2022)
The issue of civil liability arising from production of pharmaceutical factories is one of the delicate and important issues in our time. This is due to the importance of pharmaceutical products in human life and the danger it causes to his life if a mistake occurred during the manufacture of the drug. In this study, we dealt with the civil liability of the factory in light of the general rules, through the statement of the contractual and tortious responsibility of the pharmaceutical factory. It is found that that the Iraqi legislator and legislation (that we are talking about) have prevented any direct connection between the factory and the consumer and restricted the sale by official authorized. Thus, the contractual connection between the two parties is impossible to occur. Then, it is impossible to imagine the contractual responsibility of the pharmaceutical factory against the injured part. It is realized that the provisions of tort responsibility are not commensurate with the aggrieved party in terms of the drug because it is difficult to prove the mistake made by the factory. Also, it is realized that the rule of guarding things leads to factory evaded responsibility. Our research is about the objective responsibility as a basis for the responsibility of the factory. As we realized that this type of responsibility is not contractual or tortuous. But it is rather an objective responsibility based on a damage nor an error, which was approved by the French legislator and incorporated into the civil law.